A wireless trust model for healthcare. (1st September 2004) - Wickramasinghe, Nilmini; Misra, Santosh K.
In today's context of escalating costs, managed care, regulations such as the Health Insurance Portability and Accountability Act (HIPAA) and a technology savvy patient, the healthcare industry can no longer be complacent regarding embracing technologies to enable better, more effective and efficient practice management. In such an environment, many healthcare organisations are turning to m-commerce or wireless solutions. These solutions, in particular the mobile electronic patient record, have many advantages over their wired counterparts, including significant cost advantages, higher levels of physician acceptance, more functionalities as well as enabling easy accessibility to healthcare in remote geographic regions, however, they also bring with them challenges of their own. One such major challenge is security. To date, few models exist that help establish an appropriate framework, in the context of wireless in healthcare, in which to understand and evaluate all the security issues let alone facilitate the development of systematic and robust solutions. Our paper addresses this need by outlining an appropriate mobile trust model for such a scenario in healthcare organisations.